Training Issues and Strategies in Libraries, 1st edition - Gherman, Paul M. (Routledge, 2020)
This book, first published in 1990, provides analysis - applicable to any library, regardless of size - for the training and development of library personnel. Contributors from varying types of libraries, from a small private woman's college to a multinational bibliographic utility, discuss training in busy public services departments, address vendor and in-house perspectives on training for online automated systems, and examine leadership training. This practical volume provides direction for library administrators who seek to establish a climate where well-trained staff confidently and consistently perform their jobs successfully.